Precise metering pump device with multiple sensors - ZHANG LONG; KUANG TANGQING; LIU YANGYUAN; ZHANG HAO; LIU HESHENG (2022)
The utility model discloses a precise metering pump device with a plurality of sensors, which belongs to the technical field of fluid metering, and is characterized by comprising a metering pump body, a piston rod and a mechanical system, the piston rod movably extends into the metering pump body, the piston rod and the metering pump body form a piston structure, and the metering pump body is provided with a fluid outlet. Comprising a reversing valve, a ball screw device and a stepping motor. The sensor hardware system comprises a pressure sensor, an angle encoder and a displacement sensor; the microcomputer software control system comprises an acquisition card and an upper computer which are matched for use; and the sensor hardware system is electrically connected with the microcomputer software control system. The precise metering pump device with the multiple sensors is reasonable in design and layout, rapid and accurate infusion operation is facilitated, and the production efficiency and the stock solutio